One-step and room-temperature fabrication of carbon nanocomposites including Ni nanoparticles for supercapacitor electrodes - Akiyama, Tatsuya; Nakanishi, Shuhei; Yaakob, Yazid; Todankar, Bhagyashri; Pradeepkumar, Vikaskumar; Asaka, Toru; Ishii, Yosuke; Kawasaki, Shinji; Tanemura, Masaki (Royal Society of Chemistry, 2022)
With the increasing importance of power storage devices, demand for the development of supercapacitors possessing both rapid reversible chargeability and high energy density is accelerating. Here we propose a simple process for the room temperature fabrication of pseudocapacitor electrodes consisting of a faradaic redox reaction layer on a metallic electrode with an enhanced surface area. As a model metallic electrode, an Au foil was irradiated with Ar+ ions with a simultaneous supply of C and Ni at room temperature, resulting in fine metallic Ni nanoparticles dispersed in the carbon matrix with local graphitization on the ion-induced roughened Au surface. A carbon layer including fine Ni nanoparticles acted as an excellent faradaic redox reaction layer and the roughened surface contributed to an increase in surface area. The fabricated electrode, which included only 14 μg cm−2 of Ni, showed a stored charge ability three times as large as that of the bulky Ni foil. Thus, it is believed that a carbon layer including Ni nanoparticles fabricated on the charge collective electrode with an ion-irradiation method is promising for the development of supercapacitors from the viewpoints of the reduced use of rare metal and excellent supercapacitor performance.